Expert knowledge and institutional interplay : Exploring the epistemic linkages of the IPCC, IPBES, WCRP, and Future Earth - Mäkinen-Rostedt, Katri; Oreschnikoff, Aleksis; Uusikylä, Petri (Elsevier, 2025)
This article investigates the potential of knowledge interplay between epistemically driven organizations representing diverse institutional epistemologies. The concept of epistemic linkage is proposed to describe the connections that facilitate knowledge-related ties between these kinds of organizations. Epistemic linkages were mapped through experts (n = 2093) appointed to two organizations coordinating global environmental assessment processes, the Intergovernmental Panel on Climate Change (IPCC) and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), as well as two international research platforms, the World Climate Research Programme and Future Earth. Epistemic linkages form networks that underpin structures of knowledge interplay between and within the climate change and biodiversity regimes. Structural attributes of these networks, such as polycentricity, fragmentation, and complexity, were determined through the application of social network analysis (SNA). This study evaluates the network structures’ potential implications for knowledge interplay. It further illustrates the value of deliberated epistemic linkages and knowledge interplay in fostering epistemic alignment and mutual awareness. The findings reveal that epistemic linkages between IPCC and IPBES are limited, and the network is structurally constrained. The article concludes with a discussion of how the epistemic linkages have significance for coordination efforts across institutions that aim to address interconnected environmental challenges such as climate change and biodiversity loss across regimes.
Keywords: Institutional interplay; IPBES; IPCC; Social network analysis; Expert knowledge; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|